Social environments of pervasive incarceration: lessons from Australia’s top end - Western, Bruce (Tracing the relationship between inequality, crime, and punishment, 2020)
U.S. mass incarceration is characterized by pervasive imprisonment among black men with little schooling that is often viewed as the product of punitive criminal justice policy. This chapter argues that pervasive incarceration also arises under a specific set of social conditions that make police contact and detention overwhelmingly likely. This work explores the social conditions of pervasive incarceration in a significantly less punitive policy context, in Australia’s Northern Territory where social inequality is acute and incarceration is woven into everyday life. Interviews and field observation in this region show that pervasive indigenous incarceration emerges in a historical context of racial inequality marked by extreme material hardship, violent family conflict and alcohol abuse. Where violence is coupled to poverty, penal institutions respond expansively to myriad social problems - including serious violence.